Prenatal Exposure to Nonpersistent Endocrine Disruptors and Behavior in Boys at 3 and 5 Years - Philippat, Claire; Nakiwala, Dorothy; Calafat, Antonia M.; Botton, Jérémie; De Agostini, Maria; Heude, Barbara; Slama, Rémy (Environmental health perspectives, 2017)
Sex-specific associations have been reported between phthalates, bisphenol A (BPA), and child behavior. No data on large study populations are available for other phenols with possible endocrine-disrupting properties. We aimed to study associations between prenatal exposure to phthalates and several phenols on behavior among male infants. We quantified 11 phthalate metabolites and nine phenols (four parabens, benzophenone-3, BPA, two dichlorophenols, triclosan) in spot urine samples collected during pregnancy among EDEN cohort mothers who delivered a boy. Mothers completed the Strength and Difficulties Questionnaire (SDQ) when their children were 3.1 (n=529) and 5.6 (n=464) y old. BPA was positively associated with the relationship problems subscale at 3 y [incidence rate ratio (IRR): 1.11; 95% confidence interval (CI): 1.03, 1.20] and the hyperactivity-inattention subscale scores at 5 y (IRR: 1.08; 95% CI: 1.01, 1.14). Mono- -butyl phthalate (MnBP) was positively associated with internalizing behavior, relationship problem, and emotional symptom scores at 3 y. Monobenzyl phthalate (MBzP) was positively associated with internalizing behavior and relationship problems scores at 3 y. After dichotomizing SDQ scores, triclosan tended to be positively associated with emotional symptom subscales at both 3 and 5 y. The observed associations between BPA, MnBP, and behavior in boys are consistent with previous findings. Further health impact assessment studies based on dose-response functions corrected for exposure misclassification are required to quantify the public health burden possibly entailed by such associations. https://doi.org/10.1289/EHP1314.